Breaking through the clutter and the impact of ambiguous arguments on consumers' purchase decisions - Chimeziem Elijah Nwankwo-Ojionu; Nor Azura Adzharuddin; Moniza Waheed; Azlina Mohd Khir; Emem Chimeziem Elijah (Communicare)
The study explored the proliferation and codification of discursive resources related to ambiguous arguments. This has led to a point of clarification. Marketing communication scholars have purposefully neglected the impact of ambiguous arguments, focusing instead on strategic clarity. As a result, there is a lack of conceptualisation and clarity surrounding this topic. Nonetheless, studies about ambiguous arguments are still nascent because of the overbearing criticisms that ambiguity hinders effective communication and persuasion. The study experimented to investigate the impact of ambiguous arguments on consumers’ purchase decisions and demonstrated that ambiguous arguments elicit favourable purchase decisions (participants (N=260): ambiguous 130 high and 130 low). The findings reveal that highly ambiguous arguments were rated significantly more with relevance, actuality, accuracy and comprehensiveness. In addition, individuals exposed to highly ambiguous argument advertisements elicited more favourable purchase decisions than those exposed to low ambiguous argument advertisements. The findings suggest that highly ambiguous arguments (ads) undoubtedly affect consumers’ purchase decisions because of the newness, complexity and irresolvable argument presented. The motivation could not predict the relationship between ambiguous arguments and consumers’ purchase decisions. The study tested some of the key predictions of the elaboration likelihood model and strategic ambiguity model with the cues; and discovered that individuals are persuaded by central or peripheral routes based on their capacity to elaborate. The implications and future studies concerning the current theoretical framework and verifiable findings on the impacts of ambiguous arguments are carefully discussed, based on the findings.